Planejamento tributário para as clínicas médicas tributadas pelo lucro presumido: ênfase no Imposto sobre a Renda da Pessoa Jurídica (IRPJ) e Contribuição Social sobre o Lucro Líquido (CSLL) - Silva, Santina Apoliana Pereira da (2025)
The aim of this study was to analyze the current legislation that enables the reduction of the calculation basis for Corporate Income Tax (IRPJ) and Social Contribution on Net Profit (CSLL) for medical clinics taxed under the Presumed Profit regime and that provide typical hospital services. The methodology employed was qualitative research, incorporating a simulation based on a case study. The findings revealed that remaining under the Simples Nacional regime in 2024 would result in a tax increase of approximately 52.67% for the period from January to July of the calendar year. Conversely, adopting the Presumed Profit regime without applying the tax adjustment established by the Superior Court of Justice (STJ) would eliminate eligibility for the tax benefit, leading to an increase in the tax burden of around 33.73%. Based on the simulated results, the study concluded that proper tax planning is essential to ensure tax efficiency and the financial sustainability of medical clinics. This research contributes to the ongoing discussion on the importance of tax planning for medical clinics providing hospital services and highlights the critical role of accounting professionals in conducting technical analyses to identify better alternatives and even ensure the viability of such businesses